Construction of Citizenship Campaign as Peace Education for Overcoming Student Brawl (JED (Jurnal Etika Demokrasi), 2023)
This research is a construction of the idea of overcoming student brawls in Bogor city through the implementation of a citizenship campaign as a form of peace education and conflict resolution efforts as Bogor city is one of the areas where student brawls often occur and disrupt public order and security also often carried out aggressively and can be in the form of violence perpetrated by groups of students against other student groups even categorized as a crime if colored with elements of a crime. This research uses a qualitative method with data collection techniques in the form of a literature study where data collection is carried out through a review of various references related to the research focus through books, journals, and related documents using a scoping review approach. The citizenship campaign was carried out in the form of counseling on silih asih jeung silih asuh, service learning for students in Bogoh Ka Bogor, and persuasion to convey messages of peace through various media which were displayed in schools and public areas in Bogor city. Citizenship campaigns are carried out through penta helix cooperation, communication, and collaboration involving the government, academics, business, community, and the media